2022
DOI: 10.3390/foods11172713
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Different Cooking Methods on Nutrients, Antioxidant Activities and Flavors of Three Varieties of Lentinus edodes

Abstract: This work evaluated the effect of different cooking methods (boiling, steaming, microwaving, frying and pressure cooking) on the nutrients, antioxidant activities, volatile and nonvolatile taste-active components of three varieties of Lentinus edodes (808, 0912 and LM) from Guizhou Province. The results showed that LM had the most polysaccharides, 0912 had the most minerals, but LM, 808 and 0912 had low amounts of polyphenols, dietary fiber and proteins, respectively. The dietary fiber and protein were decreas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 50 publications
(74 reference statements)
0
4
0
Order By: Relevance
“…The reason may be that the exposure of button mushroom to drying at high temperatures during roasting resulted in the rapid evaporation of water and significant shrinkage of the mushroom surface, which may have allowed better retention and release of volatile components. On the other hand, the boiling treatment may have led to the partial dissolution of flavor substances into water, resulting in losses [ 5 , 32 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The reason may be that the exposure of button mushroom to drying at high temperatures during roasting resulted in the rapid evaporation of water and significant shrinkage of the mushroom surface, which may have allowed better retention and release of volatile components. On the other hand, the boiling treatment may have led to the partial dissolution of flavor substances into water, resulting in losses [ 5 , 32 ].…”
Section: Resultsmentioning
confidence: 99%
“…Different cooking methods can impart distinct effects on the aroma of food due to differences in temperature, heat transfer and heating medium [ 4 ]. In their research, Zhou et al [ 5 ] explored the impact of boiling, steaming, microwaving, deep-frying and pressure cooking on the volatile constituents of shiitake mushrooms and found that pressure cooking and deep-frying produced more aroma active compounds. Similarly, Cheng et al [ 6 ] observed that gas-frying treatments significantly contributed to the creation of flavorful substances, imparting a unique flavor to Tibetan pork.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have confirmed that nucleotides and amino acids are the main contributors to the taste of edible fungi, especially umami taste [ 1 , 35 , 36 ]. The process of cooking might lead to the structural destruction of proteins, which were degraded into primary structures, secondary structures, or into peptides [ 16 ], which can be further hydrolyzed into amino acids [ 37 ]. Due to these changes, significant upregulation of many organic acids and derivatives (mainly including amino acids, peptides, and analogues) was observed during air-frying and roasting.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, some researchers have already investigated the influence of distinct cooking methods on Lentinus edodes . These studies concluded that it was hard to maintain all nutrients at their highest levels with any cooking method [ 16 ]. The changes in the nutritional content of Lentinus edodes caused by cooking were dependent on the type of cooking method [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Using high-performance liquid chromatography (WondaSil C18; 4.6 × 250 mm, 5 μm), the mobile phase was 0.01 M KH 2 PO 4 buffer solution and methanol at a flow rate of 1 mL•min -1 . The column temperature was 25 °C and equal gradient elution was performed (Manninen et al 2018;Zhou et al 2022).…”
Section: Non-volatile Compound Analysismentioning
confidence: 99%